Outlook of university students and their profession strategy - Rajasekaran W.C.; Karthikeyan J.; Tong C.S.; Karunakaran T. (Institute of Advanced Scientific Research, Inc., 2023)
Students have been through various phases in their life wherein they have to make the toughest of choices which are going to have a huge role to play in shaping their future. The toughest of all is when they realize the lack of information regarding choice of course. This is potentially capable of destroying their life that occurs at the end of their higher secondary education. This study focuses on understanding the mentality of students undergoing arts and science programs with respect to their career plan. Previous studies conducted in relevant fields relating to our chosen topic of research specifically focused on the psychology of a student going through the process of stream selection as well as the factors that affect his or her mentality relating to the same. These include many things such as social/peer pressure, parental influence, et cetera. The students knowledge pertaining to this also plays an important role in students choice. 2019, Institute of Advanced Scientific Research, Inc.. All rights reserved.